Hereditary Cancer Program (ProCanHe): 21-years of experience at a referral registry in Argentina - Piñero, Tamara Alejandra (2019)
Registries in South America were initiated in the early 90´s with thehelp of Henry T. Lynch. The Programa de Cancer Hereditario (Pro.Can.He), is a multidisciplinary program established in 1996 at theHospital Italiano, Argentina. The aim of the study is to update our 21-year experience to determine the applicability of genetic testshighlighting the most informative molecular findings in relation toLynch syndrome mostly.Materials and methods: Families undergoing genetic testing aftergenetic counselling between1996-2018 were included. Data were obtainedfrom a prospective IRB approved database. Clinicalepidemiologicaland molecular variables were analysed. Genetic testswere carried out after a genetic counselling session and obtainingthe informed consent of the patient.Molecular testingUntil 2015, the search for variants was carried out by PCR and Sangersequencing of exons and adjacent intronic regions of MLH1 andMSH2. Then, sequencing of MLH1/MSH2/MSH6/PMS2/EPCAM geneswas performed by NGS and large rearrangements were detected byMLPA. The variants were classified according to international databases.Variants with uncertain or unreported clinical significancewere analysed In-silico using the PolyPhen, SIFT and/or Human Splicingfinder 3.0 software.ResultsA total of 83 families (49 fulfilled Amsterdam Criteria [AC] and 34 BethesdaCriteria [BC]) were analysed. Pathogenic variants were foundin 26 out of 83 (31.3%) families, been 23 pathogenic and 3 likelypathogenic.Splice site and large rearrangements represented 19.2% (5/26) and11.5% (3/26) of the variants.23% (6/26) of them were originally describedin this series and 1 was a founding mutation from Piedmont,Italy. Affected genes include MSH2, MLH1, MSH6 and PMS2 (12, 11, 2and 1 cases respectively). Mutation detection rates in AC and BT familieswere 48.9% (N=24) and 5.9% (N=2), p<0.01. Among AC families,those with identified mutation had a lower median age of cancer onset and higher incidence of extra-CCR cancer than those withoutidentified mutations. Additionally, we have also studied other genesin patients with different clinical conditions included in the registry.We identified mutations in APC, MUTYH, BMPR1A, SMAD4, CDH1,BRCA1-2, CHEK2.ConclusionThe multidisciplinary approach and the international collaborationsallowed the correct implementation of the genetic tests. To ourknowledge, this study is the first Characterization of AC families accordingto genetic tests in South America. This allowed the identificationof AC families with different ages of onset and prevalence ofextra-CRC cancers, as well as several significant variant not previouslyreported in international databases.